Por que não aprendi a falar alemão? identidade, silêncio e memória - Policarpo, Vanilda Meister Arnold Policarpo (2017)
This research approach the interdiction of the German language, that occurred in the period of the Estado Novo governed by Getúlio Vargas, between 1938 and 1945. For understand this historical period, we introduce the way as Vargas governed and the means used to create the image of the President friend, defender of the humble. Among many of the laws sanctioned in his government, we have the Law of Nationalization of Education, with prohibits classes in foreign language and, consequently, interdicts the language of the immigrant. We seek to investigate the consequences of this process in the learning of the German language for later generations as well as the effects produced in / by the memory of the subjects who lived the interdiction. For to get the objective, we realized fifteen interviews with German descendants from Santa Catarina and Rio Grande do Sul for analyze the results of the interdiction. The analyzes of the interviews suggest that there was a falt of German language learning for the younger descendants and also left traces in the memories of the descendants who lived this process.